Analisis Perbandingan Elastisitas Harga Daging Ayam Broiler dan Daging Ayam Kampung terhadap Konsumsi Rumah Tangga di Kecamatan Tarogong Kidul - Gita Anggraeni; Dara Wulansari; Rindang Rahmawan Rustandi; Muhamad Ergi Gppt; Ira Murwenie (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze and compare the price responsiveness of broiler chicken meat and native chicken meat in relation to household consumption patterns in Tarogong Kidul District, Garut Regency. A quantitative approach was employed using simple linear regression analysis based on primary data obtained through observations and interviews conducted in traditional markets. The analysis examines the extent to which price changes influence the demand for both commodities. The results indicate that broiler chicken shows a very strong relationship between price and demand, reflected in an R² value of 0.963. Statistical testing further demonstrates that price has a significant effect on broiler chicken demand (0.018 < 0.05), indicating that its demand is elastic and highly sensitive to price fluctuations. In contrast, native chicken shows an R² value of 0.698 and an insignificant price effect on demand (0.164 > 0.05), suggesting inelastic demand that remains relatively stable despite price changes. These findings reveal that consumers adjust their broiler purchase quantities more quickly in response to price changes, whereas native chicken consumption is more strongly influenced by taste preferences and habitual factors. The study concludes that there is a clear difference in price sensitivity between the two types of chicken. The implications of this research include the need for government price stabilization policies for broiler chicken to maintain household affordability, as well as quality improvement and marketing strategies for native chicken producers to strengthen competitiveness amid changing consumer demand.